Adherence to a follow-up program is improving weight loss - Elrefai, Mohamad; Vassilev, Georgi; Otto, Mirko (Bariatric surgical practice and patient care, 2017)
Background/Aim of Study: Identifying the effect of adherence to a routine postoperative follow-up program on weight loss after surgery.Methods: Eighty-six patients who underwent a bariatric procedure were included. According to their compliance to follow-up visits, patients were classified into two groups: the Drop-Out group (patients who did not attend the follow-up appointments n = 45) and regular follow-up group (patients compliant with their scheduled postoperative appointments n = 41). Both groups were compared in terms of weight loss at four fixed time points: time of operation (T0), next to last (T1), last follow-up appointments (T2), and time of interview (T3).Results: Weight decreased in the time interval between T0 and T2 without a significant difference between both groups. A significant difference, however, was observed during the time interval T2 to T3, as weight continued to decrease among the regular follow-up patients versus a rise within the Drop-Outs patients (62.7 ± 24.1% vs. 49.9 ± 22.9%; p = 0.014).Conclusion: Adherence to a follow-up program is crucial to improve and sustain weight loss.